Suplementação de unha-de-gato (Uncaria tomentosa) em dietas para tilápias-do-Nilo e acará-bandeira (Pterophyllum scalare) - Cala Delgado, Daniel Leonardo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Cat's claw (Uncaria tomentosa) is an Amazonian plant that presents anti-inflammatory properties. Previous studies have shown an increase in the productive performance of Nile tilapia; however, fish presented liver alterations. This study aimed to evaluate the performance and toxicological aspects in Nile tilapia and freshwater angelfish fed diets supplemented with cat's claw. In the study with Nile tilapia were tested supplementation levels of 0; 150; 300; 450 mg of cat's claw/Kgof feed, and the assessment of Nile tilapia was in a randomized block design (weight) with four replications. In the initial assessment, there were two biometrics (30 days and 60 days) to evaluate growth performance, collection of blood and organs (liver, kidney, spleen). In the study with angelfish, were studied levels of 0; 75; 150; 300; 450 mg of cat's claw/Kg of diet in a completely randomized design.For the analysis of growth performance and collection of organs were collected every 30 days for 5 months, and in the last month fish were submitted to simulations of transport for 24 hours. After that, they were evaluated blood glucose, mortality and water quality parameters. In the study with Nile tilapia, at 30 days, fish presented a reduction in feed mean intake and feed conversion in the groups fed diets containing cat's claw. Total protein and globulin were higher in the group fed 450 mg/Kg. Other parameters did not differ (p> 0.05) between treatments. At 60 days,Nile tilapia supplemented with the plant did not show differences in growth performance and blood countcompared to the control group. At 30 days there was no difference between treatments for blood glucose, but this same parameter at 60 days was lower in the treatment 450 mg/kg compared with control group.In the test of hepatic functionality, the levels of aspartate transaminase (AST), total protein (TP) and globulin were higher in the groups supplemented with cat's claw, as well as liver ...

A unha-de-gato (Uncaria tomentosa) é uma planta amazônica que apresenta propriedadesanti-inflamatórias. Estudos prévios demonstraram aumento no desempenho produtivo em tilápias-do-Nilo, porém os peixes apresentaram alterações hepáticas. Este trabalho teve por objetivo avaliar o desempenho produtivo e aspectos toxicológicos emtilápias-do-Nilo e acará-bandeira, alimentados com dietas suplementadas com unha-de-gato.No estudo com tilápias-do-Nilo foram testados níveis de suplementação 0; 150; 300; 450 mg de unha-de-gato / kg-1 de ração, sendo a avaliação das tilápias em delineamento em blocos casualizados (peso), com quatro repetições. Além da avaliação inicial, foram realizadas duas biometrias (30 dias e 60 dias) para avaliar desempenho produtivo, coleta de sangue e órgãos (fígado, rim, baço). No estudo com acará-bandeira, foram estudadas os níveis de0; 75; 150; 300; 450 mg de unha-de-gato / kg de ração, em um delineamento inteiramente casualizado.Para as análises de desempenho produtivo e coleta de órgãos foram realizadas biometrias a cada 30 dias durante 5 meses, sendo que no último mês os peixes foram submetidos à simulação de transporte por 24 horas. Posteriormente, foram avaliados a glicemia sanguínea, mortalidade e parâmetros de qualidade da água.No estudo com tilápias-do-Nilo, aos 30 dias, os peixes apresentaram redução no consumo médio de ração e conversão alimentar aparente nos grupos alimentados com dietas contendo unha-de-gato. A proteína total e globulina foram maiores no grupo arraçoado com a concentração de 450 mg/kg. Os demais parâmetros avaliados não apresentaram diferença (p>0,05) entre os tratamentos. Aos 60 dias as tilápias suplementadas com a planta não apresentaram diferenças no desempenho produtivo e na avaliação da série vermelha quando comparados ao grupo controle.Aos 30 dias não houve diferença entre os tratamentos para glicemia, mas este mesmo parâmetro...
Keywords: Peixe - Criação; Tilápia-do-Nilo; Matéria médica vegetal; Desempenho; Histologia; Figado; Fishes